Changed crossmodal functional connectivity in older adults with hearing loss. (January 2017) - Puschmann, Sebastian; Thiel, Christiane M.
Abstract: Previous work compellingly demonstrates a crossmodal plastic reorganization of auditory cortex in deaf individuals, leading to increased neural responses to non-auditory sensory input. Recent data indicate that crossmodal adaptive plasticity is not restricted to severe hearing impairments, but may also occur as a result of high-frequency hearing loss in older adults and affect audiovisual processing in these subjects. We here used functional magnetic resonance imaging (fMRI) to study the effect of hearing loss in older adults on auditory cortex response patterns as well as on functional connectivity between auditory and visual cortex during audiovisual processing. Older participants with a varying degree of high frequency hearing loss performed an auditory stimulus categorization task, in which they had to categorize frequency-modulated (FM) tones presented alone or in the context of matching or non-matching visual motion. A motion only condition served as control for a visual take-over of auditory cortex. While the individual hearing status did not affect auditory cortex responses to auditory, visual, or audiovisual stimuli, we observed a significant hearing loss-related increase in functional connectivity between auditory cortex and the right motion-sensitive visual area MT+ when processing matching audiovisual input. Hearing loss also modulated resting state connectivity between right area MT+ and parts of the left auditory cortex, suggesting the existence of permanent, task-independent changes in coupling between visual and auditory sensory areas with an increasing degree of hearing loss. Our data thus indicate that hearing loss impacts on functional connectivity between sensory cortices in older adults.